Perancangan Sistem Informasi Investaris Barang di SMP Negeri 1 Tanasitolo Kabupaten Wajo - Suwandi, Ihsanulfu'ad; Rachmat, Zul; S, Wahyuddin (Jurnal Bisnis Digital dan Enterpreneur (BISENTER), 2023)
SMP N 1 Tanasitolo uses inventory data processing which is still manual, where the recording of goods is still done on paper and data storage media is stored in archives. Supporting employee performance and goods inventory activities requires the application of an inventory information system as a means for the needs of employees within the scope of SMP N 1 Tanasitolo in their activities by looking at the development of information technology and the increasingly complex demands of employees, the development and utilization of information technology is very important. This study aims to design an inventory information system based on Visual Basic 6.0. The system is designed in several parts: recording incoming and outgoing goods, recording inventory data, transferring goods and preparing inventory reports. Using the Visual Basic programming language and MySQL as the database. The system development method uses the waterfall method. Data collection was obtained through observation, interviews and literature studies. The result of the implementation of this inventory information system is that recording inventory data and making inventory reports are easier to do. With this inventory information system, inventory data collection work at SMP Negeri 1 Tanasitolo can be done more quickly and accurately.